The modified alpha power law based model of statistical fluctuation in nanometer FGMOSFET. Issue 1 (1st January 2018) - Banchuin, Rawid
Abstract: The modified alpha power law based model of statistical fluctuation in drain current of an unconventional Metal Oxide Semiconductor Field Effect Transistor namely Floating-Gate Metal Oxide Semiconductor Field Effect Transistor (FGMOSFET) has been proposed where the nanometer FGMOSET have been focused. Unlike the previous works, the fluctuation in drain current has been expressed in a per-unit basis which is able to show the true criticality of such fluctuation, and those previously assumed approximations on FGMOSFET's parameters have not been adopted. The process induced device level statistical fluctuations and the related correlations have been taken into account. Nonlinearity of voltage at the floating gate and dependency on voltage at the drain terminal of the coupling factors have also been concerned. The proposed model can accurately fit the 65 nm 4th generation Berkeley Short-channel IGFET Model (BSIM4) based reference obtained from the Monte-Carlo simulation by using FGMOSFET Simulation Program with Integrated Circuit Emphasis based simulation technique. If desired, it can fit those references based on smaller technologies by using the optimally extracted drain current parameters of those technologies. From our model, the statistical fluctuation reducing strategies of nanometer FGMOSFET can be obtained. Moreover, the application of the model to the candidate nanometer FGMOSFET based circuit has also been shown.